A10.04 7WISP1, a downstream mediator of canonical wnt signalling, induces pathology in experimental osteoarthritis and predicts disease progression in early osteoarthritis patients. (24th February 2016) - van den Bosch, MH; Blom, AB; Maeda, A; Kilts, TM; van den Berg, WB; Lafeber, FP; van Lent, PL; Young, MF; van der Kraan, PM
Abstract : Background: An important role for canonical Wnt signalling in osteoarthritis pathology has been established. However, the role of Wnt1-induced secreted protein-1 (WISP1), which we found increased in experimental and human OA, remains to be elucidated. Here, we determined the relation between WISP1 expression and OA-progression in early OA patients. Additionally, we determined how WISP1 might be involved in OA pathology using experimental OA models. Methods: WISP1 expression levels, determined with microarray analysis on synovial biopsies obtained from patients enrolled in the CHECK study of early OA patients, were coupled to OA-progression. Progression was defined as ≥1mm decrease in joint space width and ≥4x increased osteophyte size after 5 years. Human OA synovium was stimulated with WISP1. Joint pathology was assessed after induction of experimental OA models (DMM, ACLT and CIOA) in WT or WISP1-deficient mice. Immunohistochemical staining was used to visualise NITEGE aggrecan neoepitopes resulting from protease activity. Gene expression was evaluated using qRT-PCR. Results: WISP1 expression at baseline was significantly higher in CHECK patients that showed OA-progression between baseline and the five-year follow-up measurement compared to non-progressors. Stimulation of human OA synovium with WISP1 increased the expression of the proteases MMP-2/-3/-9/-13 and ADAMTS-4/-5. To further pinpoint the role of WISP1 during OA, we induced three experimental OA models with different characteristics in WT and WISP1-deficient mice. We observed significantly decreased cartilage damage in the tibio-femoral joints of WISP1-deficient mice, compared with the WT controls in all models. Accordingly, we found decreased expression of MMP-3/-9 and the aggrecanases ADAMTS-4 and -5 in synovial tissue from WISP1-deficient mice. Moreover, we observed decreased expression of IL-1 and IL-6, which have the potential to induce protease expression, but not of the anti-inflammatory cytokine IL-10 in the WISP1-deficient mice. Finally, the protease activity in the cartilage, as assessed by the staining of the neoepitope NITEGE, was decreased in the WISP1-deficient mice. Conclusions: Increased WISP1 expression in OA joints may play an important role in OA pathology via increased expression of MMPs and ADAMTSs in the synovium. Specific downregulation of WISP1 may avoid undesired side-effects that are likely to occur after targeting upstream Wnt signalling.